(untitled) (Third Sector Social Economic Review, 2024)
The concept of quiet quitting is used to describe the situation where employees who are not happy with their jobs continue their jobs with minimum effort instead of quitting. This concept is used for employees who continue their jobs without engaging in extra-role behaviors outside of their designated jobs. These employees also seek a balance between their work and life. Quiet quitting later occurred with the claims that the employee could simplify their work life and career so that they could devote more of their time to other areas of life. In this context, this study aims to determine the effect of quiet quitting on work-life balance. For this purpose, 411 people working in the health sector were reached voluntarily on the basis of convenience sampling. The correlation analysis revealed a moderately significant positive relationship between quiet quitting and work-life balance with r=0.129 (p<0.05 significance level). Regression analysis revealed a positive effect of quiet quitting on work-life balance (β=0.105; p<0.05). In the findings obtained as a result of the difference tests (t-test, ANOVA) on the perceptions of quiet resignation, significant differences were found between gender, status, age, education and working hours at p<0.05 level of significance. In the other findings obtained as a result of the difference tests on work-life balance, no significant differences were found between the gender, status, age, education and working hours of the employees at p<0.05 level of significance